Menatap Barat dengan Kaca Mata Islam: Perbedaan Pendekatan Gus Baha dan Ustadz Abdul Somad - Muhammad Riza Fajrul Azhar; Antyesti; Yeni Kartika; Melly Kurnia; Alihan Sastra (CV. Doki Course and Training, 2025)
ABSTRACT This study discusses the differences in approach between Gus Baha and Ustadz Abdul Somad in responding to Western phenomena through the lens of Islam. Gus Baha, a NU cleric who is known for his moderate and inclusive approach, tends to prioritize dialogue and cultural understanding to bridge differences. He emphasizes the importance of morals and ethics in interacting with Western values. On the other hand, Ustadz Abdul Somad, with a more assertive and orthodox approach, often criticizes the negative influence of Western culture and calls for the implementation of more conservative Islamic values. His approach emphasizes the implementation of sharia and maintaining identity as a response to external influences. Through this analysis, it is hoped that readers can understand how these two figures make different contributions in responding to the challenges of globalization and foreign values, as well as their impact on Muslim society in Indonesia. Abstrak: Penelitian ini membahas perbedaan pendekatan antara Gus Baha dan Ustadz Abdul Somad dalam menanggapi fenomena Barat melalui kacamata Islam. Gus Baha, seorang ulama NU yang terkenal dengan pendekatannya yang moderat dan inklusif, cenderung mengedepankan dialog dan pemahaman budaya untuk menjembatani perbedaan. Ia menekankan pentingnya akhlak dan etika dalam berinteraksi dengan nilai-nilai Barat. Di sisi lain, Ustadz Abdul Somad, dengan pendekatan yang lebih tegas dan ortodoks, seringkali mengkritik pengaruh negatif dari budaya Barat dan menyerukan penerapan nilai-nilai Islam yang lebih konservatif. Pendekatannya menekankan pada penerapan syariat dan penjagaan identitas sebagai respons terhadap pengaruh luar.